A theoretical review on the origin of medicinal practices in humans: echoes from evolution - Ferreira Júnior, Washington Soares; Albuquerque, Ulysses Paulino (Ethnobiology and Conservation, 2018)
Humans have been coping with diseases throughout the evolutionary history. The emergence of medical systems, which integrate knowledge and practices related to health management, can be assumed as one of the reactions of the human species to respond to the pressures of diseases. An intriguing question is related to the understanding of how these systems have emerged in our species. To answer this question, some authors created scenarios to explain the origin of these systems, from an ecological and evolutionary logic. In this article, we briefly introduce some of the key ideas linked to these scenarios and how they may be important in guiding ethnobiology research.